Providing spatial decision support for evacuation planning: a challenge in integrating technologies - Silva, F. Nisha de (2001)
Computer-aided decision-support tools are part and parcel of the emergency planning and management process today. Much is dependent on using modern technology to gather and analyse data on damage assessment, meteorology, demography, etc. and provide decision support for prevention/mitigation, response and recovery. Diverse technologies are merged to provide useful functions to aid the emergency planner/manager. Complexities arise when attempting to link several streams of technology to achieve a realistic, usable and reliable decision-support tool. This discussion identifies and analyses the challenging issues faced in linking two technologies; simulation modelling and GIS, to design spatial decision-support systems for evacuation planning. Experiences in designing CEMPS, a prototype designed for area evacuation planning, are drawn on to discuss relevant managerial, behavioural, processual and technical issues. Focus is placed on modelling evacuee behaviour, generating realistic scenarios, validation, logistics, etc. while also investigating future trends and developments. - Reproduced
Keywords: Disaster prevention